Mechanism of Allosteric Modulation of the Cys-loop Receptors - Paul Whiteaker; Yao Huang; Yongchang Chang (MDPI AG, 2010)
The cys-loop receptor family is a major family of neurotransmitter-operated ion channels. They play important roles in fast synaptic transmission, controlling neuronal excitability, and brain function. These receptors are allosteric proteins, in that binding of a neurotransmitter to its binding site remotely controls the channel function. The cys-loop receptors also are subject to allosteric modulation by many pharmaceutical agents and endogenous modulators. By binding to a site of the receptor distinct from the neurotransmitter binding site, allosteric modulators alter the response of the receptors to their agonists. The mechanism of allosteric modulation is traditionally believed to be that allosteric modulators directly change the binding affinity of receptors for their agonists. More recent studies support the notion that these allosteric modulators are very weak agonists or antagonists by themselves. They directly alter channel gating, and thus change the distribution of the receptor across multiple different affinity states, indirectly influencing receptors' sensitivity to agonists. There are two major locations of allosteric modulator binding sites. One is in subunit interfaces of the amino-terminal domain. The other is in the transmembrane domain close to the channel gating machinery. In this review, we also give some examples of well characterized allosteric binding pockets.